Bunnicula : the graphic novel - Howe, James; Donkin, Andrew; Gilpin, Stephen; Howe, Deborah, 1946-1978. (2022)
Though scoffed at by Harold the dog, Chester the cat tries to warn his human family that their foundling baby bunny must be a vampire. Presented in comic book format.
Ages 8-12.
Grades 4-6.
Keywords: Rabbits -- Comic books, strips, etc; Vampires -- Comic books, strips, etc; Pets -- Comic books, strips, etc; Graphic novels; Graphic novels; Comics (Graphic works); Detective and mystery comics